Horizontal Integration in the Agricultural Sector as a Factor Increasing Its Competitiveness – Experience from Poland - Karolina Pawlak, Karolina Pawlak; Kołodziejczak, Małgorzata; Xie, Yumei (Eastern European Countryside, 2024)
The aim of this article is to present the process of the development of horizontal integration in the agricultural sector in Poland in relation to the increase in its competitiveness. The article uses the data of the National Cooperative Council in Poland, The Agency for Restructuring and Modernisation of Agriculture, as well as Central Statistical Office in Poland. The process of formation of agricultural producer groups accelerated considerably when Poland joined the EU, especially due to the possibility to receive support from public funds. In 2013, at the end of the first full financial framework 2007–2013, there were almost 1300 agricultural producer groups in Poland. The most of them functioned in central, western and north-western regions, where larger and specialised farms are prevalent and where farmers understand the need for joint activity and want to gain a possibility to generate both technological and cost and price advantages and to increase the profitability of production. So far Polish producers of cereals, oilseeds, pigs and poultry have been relatively best organised. In 2017 about 45% of all registered groups of agricultural producers had the status of cooperatives. In pigs and beef cattle production the share of cooperatives in the total number of registered groups was even higher and amounted to 70% and 83%, respectively. Such groups are capable of helping farmers to solve the problems of how to sell their products, to ensure the appropriate quality of those products and to increase the cost-effectiveness of production. Cooperatives are often involved in social, educational and cultural activities provided to their members and rural community. Therefore, it can be said that very presence of cooperatives favours the development of agriculture in a particular region and in the entire country.